Strengthening Entrepreneurial Skills to Support Economic Rights of Women with Disabilities in Digital-Based MSMEs in Cirebon City - Ratna Puspitasari; Mukhlisoh Mukhlisoh; Amanda Dini Nurul Qolby (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
Women with disabilities often face multiple layers of discrimination that limit their economic roles and participation. A qualitative approach through a descriptive explanatory case study method was carried out to understand the dynamics of the social context, the subjective experiences of participants, and practices surrounding the entrepreneurial activities of women with disabilities. Thematic data analysis of Miles and Huberman's interactive model with the hope of: first mapping the profile and challenges so that the expected research results are able to map the profile and specific challenges faced by women with disabilities as digital MSME actors in Cirebon City; second, identifying the form and effectiveness of skill improvement programs; third describing the mechanisms and results of strengthening economic rights: increased income, independence and market access. The amount of partiscipant in this study is about 30 participant. Novelty, on the integration of disability perspectives, digital entrepreneurship and strengthening of economic rights in the local context of Cirebon City which has not been widely discussed comprehensively. Outcome: increasing the economic capacity of women with disabilities, expanding access to digital markets, and strengthening sustainable economic independence